2020
DOI: 10.1177/1540415320921489
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Latino Health: A Systematic Review of Risk and Resilience

Abstract: Introduction: As anti-immigrant hostility toward Latino populations grows, more fervent attention is needed to consider strength-based approaches to attenuate the effects of perceived discrimination. This systematic review synthesizes the evidence about the effects of racial/ethnic discrimination on mental, physical, and health behaviors of Latinos and examines the coping mechanisms and cultural factors that attenuate the negative association between discrimination and health among adult Latinos living in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 68 publications
3
52
0
Order By: Relevance
“…In addition, in a sample of 150 pregnant Latina women (mean age ¼ 27.6 years), investigators found approximately 44% of participants reported experiencing some form of everyday discrimination in their lifetimes (Santos et al, 2018). A recent systematic review of 33 studies found that perceived discrimination is consistently associated with a higher prevalence of depressive symptoms and substance use among Latinos across studies (Andrade et al, 2020). However, research investigating the associations of discrimination with physical health conditions, such as hypertension and diabetes, in Latinos is limited and mixed (Andrade et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in a sample of 150 pregnant Latina women (mean age ¼ 27.6 years), investigators found approximately 44% of participants reported experiencing some form of everyday discrimination in their lifetimes (Santos et al, 2018). A recent systematic review of 33 studies found that perceived discrimination is consistently associated with a higher prevalence of depressive symptoms and substance use among Latinos across studies (Andrade et al, 2020). However, research investigating the associations of discrimination with physical health conditions, such as hypertension and diabetes, in Latinos is limited and mixed (Andrade et al, 2020).…”
mentioning
confidence: 99%
“…A recent systematic review of 33 studies found that perceived discrimination is consistently associated with a higher prevalence of depressive symptoms and substance use among Latinos across studies (Andrade et al, 2020). However, research investigating the associations of discrimination with physical health conditions, such as hypertension and diabetes, in Latinos is limited and mixed (Andrade et al, 2020).…”
mentioning
confidence: 99%
“…Recent years have seen an increase in anti-immigrant attitudes, specifically directed at Latinx groups (Newman et al, 2018), resulting in a need to better understand the negative psychological consequences associated with ethnic discrimination among Latinxs. Consistent evidence has shown a robust relationship between ethnic discrimination and depression with Latinx samples (Andrade et al, 2021). For example, a meta-analysis reported a statistically significant effect size in Latinx studies linking ethnic discrimination with increased depression symptoms (Lee & Ahn, 2012).…”
Section: Ethnic Discrimination and Mental Healthmentioning
confidence: 97%
“…Although the rejection-identification model of stigma has received mixed support, research has supported this model among Latinx individuals specifically (Armenta & Hunt, 2009). Increasing ethnic identification may help buffer individuals from the aversive impact stigmatization might otherwise have on mental health (Andrade et al, 2020). This has shown to be true in terms of personal discrimination (Mossakowski, 2003; Williams et al, 2014) and group-based discrimination (Osborne et al, 2015).…”
Section: Anti-latinx Stigma In the United Statesmentioning
confidence: 99%